Design and synthesis of novel caffeic acid phenethyl ester (CAPE) derivatives and their biological activity studies in glioblastoma multiforme (GBM) cancer cell lines - Sucu, Bilgesu Onur; Koc, Elif Beyza; Ipek, Ozgecan Savlug; Mirat, Afranur; Almas, Furkan; Guzel, Melike Aybala; Dogan, Berna; Uludag, Damla; Karakas, Nihal; Durdagi, Serdar; Guzel, Mustafa (ELSEVIER SCIENCE INC, 2022)
Glioblastoma Multiforme (GBM) is the most aggressive brain tumor and classified as one of the deadliest cancers. The current treatment plans for GBM remains to be ineffective because of its rapid progress and inability of the drugs used to cross the blood-brain barrier (BBB). Thus, developing more effective and potent medicines for GBM are needed. There have been several reports demonstrating that CAPE presents reasonably good anti-cancer activity in certain cancer cell lines and can penetrate the blood-brain barrier. Accordingly, in this study we synthesized several novel CAPE analogs with the addition of more druggable handles and solubilizing entities and subsequently evaluated their in vitro therapeutic efficacies in GBM cell lines (T98G and LN229). The most potent compound was then examined extensively and results showed that the 50 mu M novel CAPE analog (compound 10) significantly decreases the viability of both T98G and LN229 GBM cells as compared to CAPE itself. Moreover, the compound 10 was not cytotoxic to healthy human cells (fibroblast-like mesenchymal stem cells) at the same concentration. Apoptotic (32.8%, and 44.6%) cell populations were detected in the compound 10 treated groups for LN229 and T98G, respectively. As an indication of apotosis, significantly increased PARP cleavage was detected in compound 10 versus CAPE treated LN229. In addition, we conducted molecular docking and molecular dynamics (MD) simulations studies on certain targets playing roles on GBM disease pathway such as NF-kappa B, EGFR, TNF-alpha, ERK2, PAPR1, hCA IX and hCA XII. Our findings demonstrated that designed CAPE analogs have anti-cancer activity on GBM cells and in silico studies also demonstrate the inhibitory ability of suggested compounds via interactions with critical residues in binding pockets of studied targets. Here, we suggest the novel CAPE analog to study further against GBM. Therefore, identification of the compound related molecular signature may provide more to understand the mechanism of action.
Keywords: Caffeic acid phenethyl ester (CAPE); Novel heterocyclic CAPE analogs; Anti-cancer activity; Glioblastoma multiforme (GBM); In silico molecular modeling; ACCURATE DOCKING; PROTEIN; ACTIVATION; MECHANISM; GLIDE; Biochemistry & Molecular Biology; Computer Science; Crystallography; Mathematical & Computational Biology